1995
DOI: 10.1093/carcin/16.8.1723
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of butadiene monoepoxide and butadiene diepoxide in various tissues of rats and mice following a low-level inhalation exposure to 1,3-butadiene

Abstract: 1,3-Butadiene (BD), a chemical used extensively in the production of styrene-butadiene rubber, is carcinogenic in Sprague-Dawley rats and B6C3F1 mice. Chronic inhalation studies revealed profound species differences in the potency and organ-site specificity of BD carcinogenesis between rats and mice. BD is a potent carcinogen in mice and a weak carcinogen in rats. Previous studies from our laboratory and others have shown marked differences between rats and mice in the metabolism of BD, which may account for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(52 citation statements)
references
References 0 publications
2
48
1
1
Order By: Relevance
“…These results are strengthened by reports on the DNA adducts from EB and EBdiol, showing that approximately the same level of the respective adduct was present in all tissues examined (33,34). However, the concentrations of the epoxide metabolites in organs were found to be one half of the concentration in blood (32). This has earlier also been shown for the chemically related compound ethylene oxide through the comparison of Hb-and DNA-adduct levels (35).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…These results are strengthened by reports on the DNA adducts from EB and EBdiol, showing that approximately the same level of the respective adduct was present in all tissues examined (33,34). However, the concentrations of the epoxide metabolites in organs were found to be one half of the concentration in blood (32). This has earlier also been shown for the chemically related compound ethylene oxide through the comparison of Hb-and DNA-adduct levels (35).…”
Section: Discussionsupporting
confidence: 58%
“…To estimate a common risk coefficient, b, for all tumor sites on the basis of dose in blood, it is a necessity that the cancer causative agent(s) is (are) evenly distributed in the different organs. Measurements of the concentrations of EB and DEB in mice and rats after a 4-hour exposure to 62.5 ppm BD in earlier studies have shown that the concentration of the respective epoxide is similar in all vessel-rich organs (32). These results are strengthened by reports on the DNA adducts from EB and EBdiol, showing that approximately the same level of the respective adduct was present in all tissues examined (33,34).…”
Section: Discussionmentioning
confidence: 82%
“…Albrecht et al (48) exposed mice and rats at 0, 50, 200, 500, and 1300 ppm and showed a nonlinear dose response in mice at concentrations above 200 ppm and a linear dose response for rats. The adduct data are in general agreement with concentrations of epoxybutene measured in blood and tissues that were lower in rats than in mice exposed to butadiene (42)(43)(44)50 (47). The workers, all nonsmokers, were divided into two groups on the basis of work location.…”
Section: Hemoglobin Adductssupporting
confidence: 77%
“…Diepoxybutane could not be detected in livers of mice or lungs and livers of rats. Thornton-Manning et al (44) recently reported that concentrations of epoxybutene were 3 to 74 times greater in tissues of mice compared with rats following exposure to 62.5 ppm butadiene for 4 hr. Levels of diepoxybutane in blood and tissues of rats were 40-to 163-fold lower than in corresponding mouse tissues.…”
Section: Introductionmentioning
confidence: 98%
“…In chronic inhalation experiments with B6C3F1 mice and Sprague-Dawley rats, BD was carcinogenic in both species (10,28). However, B6C3F1 mice developed tumors at BD exposure concentrations three orders of magnitude lower than those that cause cancer in Sprague-Dawley rats (10,(28)(29)(30). Furthermore, the mutational spectrum found in BD-induced tumors of mice was different from that in rats (31).…”
Section: Introductionmentioning
confidence: 99%